Penerapan Diversi Pada Anak Sebagai Pelaku Tindak Pidana Di Indonesia - Selly Patria Amanda (CV. ITTC INDONESIA, 2024)
This article discusses child protection in the context of Indonesian law, with a focus on the Child Protection Law and the Juvenile Criminal Justice System. The main issues raised are the need to protect children from violence and negative stigma, as well as the challenges in implementing diversion as an alternative to resolving children's cases. The formulation of the problem includes the application of diversion to protect children's rights and the role of law enforcement officials in this process The research method used is normative law, by analyzing existing regulations and implementation challenges, such as lack of parental support and coordination between institutions. The results show that diversion aims to rehabilitate children without reducing criminal liability, although its implementation still faces obstacles. The conclusion emphasizes the importance of a restorative justice approach in the juvenile criminal justice system to provide a more holistic solution, as well as the need for efforts to overcome obstacles to make the implementation of diversion more effective.